Crystal structure of 8,8′-di-p-tolyl-8′H-7,8′-biacenaphtho[1,2-d]imidazole, C40H26N4 - Al-Dies, Al-Anood M.; Asiri, Abdullah M.; Khan, Salman A.; Tiekink, Edward R. T. * (de Gruyter, 2019)
The crystal structure is shown in the figure. Tables 1 and 2 contain details on crystal structure and measurement conditions and a list of the atoms including atomic coordinates and displacement parameters.